Energy Security - Karen Hogan (National Competitiveness and Productivity Council (NCPC), 2022)
The NCPC believes that access to reliable, affordable supplies of energy is critical for Ireland's future wellbeing and long-term competitiveness. To meet growing demand for energy in Ireland and address increased supply uncertainty, the NCPC believes that there should be an urgent focus on projects to help diversify energy supply sources and investing in upgrading our electricity infrastructure. It is crucial that policies to enhance energy security align with the targets set out in the Climate Action Plan 2021 to facilitate Ireland's transition to a low carbon economy.
Keywords: 330